Hubungan Sanitasi Dasar dengan Kejadian Stunting pada Anak SD di Loa Janan Ilir Samarinda - Yuning Tyas Nursyah Fitri; Rini Ernawati; Alfi Ari Fakhrur Rizal (Poltekkes Kemenkes Padang, 2024)
Stunting school children is a long-term result of food deficiencies combined with environmental problems, caused indirectly by factors, one of which is environmental factors in basic sanitation. Purpose of knowing the relationship between basic sanitation and the incidence of stunting in school-age children in elementary schools in Loa Janan Ilir sub-district. Type of research is descriptive correlation with a cross sectional approach. Sampling using Stratified Proportional Random Sampling with a total sample that met the inclusion criteria of 188 respondents. Inclusion criteria for this study are: Children aged 6 - 8 years of grade 1 (ABC), their Parents / Guardians who are willing to become respondents at SDN 008, 009, 010, MI DDI Tani Aman, MI Ar-Rahmah in Loa Janan Ilir Samarinda District. Exclusion criteria for this study were: First grade children (ABC) SDN 008, 009, 010, MI DDI Tani Aman, MI Ar-Rahmah Loa Janan Ilir Samarinda District who were sick or absent, parents/guardians of students who were not present. Data analysis using the Chi- Square test obtained results, clean water supply (p value = 0.033 <0.05), latrine use (p value = 0.044 <0.05) and wastewater disposal (p value = 0.004 <0.05), the conclusion is that there is a relationship between basic sanitation consisting of clean water supply, latrine use and wastewater disposal with the incidence of stunting in school-age children in elementary schools in Loa Janan Ilir Samarinda District.